The effect of post‐stroke hyperglycaemia on the levels of brain damage and repair‐related circulating biomarkers: the Glycaemia in Acute Stroke Study II. (17th June 2019) - Otero‐Ortega, L.; Gutiérrez‐Fernández, M.; Gutiérrez‐Zúñiga, R.; Madero‐Jarabo, R.; Alonso de Leciñana, M.; Laso‐García, F.; Lisbona, A.; Delgado‐Mederos, R.; Gállego‐Culleré, J.; Martínez‐Zabaleta, M.; Freijo, M.; Portilla, J. C.; et al.
Abstract : Background and purpose: The aim was to identify whether post‐stroke hyperglycaemia (PSH) influences the levels of circulating biomarkers of brain damage and repair, and to explore whether these biomarkers mediate the effect of PSH on the ischaemic stroke (IS) outcome. Methods: This was a secondary analysis of the Glycaemia in Acute Stroke II study. Biomarkers of inflammation, prothrombotic activity, endothelial dysfunction, blood–brain barrier rupture, cell death and brain repair processes were analysed at 24–48 h (baseline) and 72–96 h (follow‐up) after IS. The associations of the biomarkers and stroke outcome (modified Rankin Scale score at 3 months) based on the presence of PSH were compared. Results: A total of 174 patients participated in this sub‐study. Brain‐derived neurotrophic factor (BDNF) at admission was negatively correlated with glucose levels. PSH was associated with a trend toward higher levels of endothelial progenitor cells (EPCs) at baseline. The EPCs in the PSH group then decreased in the follow‐up samples (−8.5 ± 10.3) compared with the non‐PSH group (4.7 ± 7.33; P  =   0.024). However, neither BDNF nor EPC values had correlation with the 3‐month outcome. Higher interleukin‐6 at follow‐up was associated with poor outcomes (modified Rankin Scale > 2) independently of PSH. Conclusion: Post‐stroke hyperglycaemia appears to be associated with a negative regulation of BDNF and a different reaction in EPC levels. However, neither BDNF nor EPCs showed significant mediation of the PSH association with IS outcome, and only higher interleukin‐6 in the follow‐up samples (72–96 h) was related to poor outcomes, independently of PSH status. Further studies are needed to achieve definite conclusions.